Papéis e competências do líder: um estudo em organização multinacional francesa - Freitas, Dante Bonetti de (2007)
Leadership is considered one of the most fundamental factors in obtaining results in nowadays organizations. The competencies the leader needs are at the center of discussion in generally all big companies. Of the various theories that discussed leadership and leader competencies over the last few years, there is one outstanding theory called the competitive value model , developed by Quinn (2003). This theory states there are 24 fundamental leader competencies and eight roles related to these competencies, which give us a broad idea on the subject. The purpose of this study is to identify the development level of the leader competencies and the roles in the construction material sector of a French multinational company head office. To do that, a research was carried out among leaders of the company head office, to identify which of the four development levels each of the 24 leader competencies and eight roles had. By using a questionnaire and interviews it was possible to measure the competencies development level and suggest actions to improve it. The obtained results show us that 14 competencies reached the developed level and 10 competencies reached the less developed level. From this data it is possible to identify where it is necessary to prioritize the leaders development in order to improve the competencies and consequently the business results in the organization